Sorrentino, Loro and the Others: The contemporary Italian Auteur in the French Context - Coladonato, Valerio (Cinergie – Il Cinema e le altre Arti, 2020)
This article analyses the circulation and reception of Paolo Sorrentino’s Loro/Silvio et les autres (2018) in France, as a case study that complements recent surveys of contemporary Italian cinema’s global impact. The film’s commercial failure is taken as a cue to observe the intermediaries between Italian films and French audiences. The institutional logics underlying the notion of “Italian auteur cinema”, the interpretive categories associated to it — such as political commitment or impegno —, and the stratification of taste in France are also discussed. To this purpose, the article brings together three points of view (and as many methodological approaches): first, it contextualizes auteur cinema as a specific type of cultural consumption by French spectators; then, it looks at the media circulation of contents related to Loro/Silvio et les autres and summarizes its critical reception; finally, it provides an account of its participation in festivals, through interviews with cultural operators who promote Italian cinema in France. What emerges is that, whereas the French market is globally favorable to Italian auteur cinema, the success of each film depends on the ability to intercept a core group of spectators, through the habits, values and intermediaries legitimized by French cinephile culture.